Screening of active components in Astragalus mongholicus Bunge and Panax notoginseng formula for anti-fibrosis in CKD: nobiletin inhibits Lgals1/PI3K/AKT signaling to improve renal fibrosis - Fang Yang; Tong Li; Xiao-qian Zhang; Yi Gong; Hongwei Su; Junming Fan; Li Wang; Qiong-dan Hu; Rui-zhi Tan (Renal Failure)
The Astragalus mongholicus Bunge and Panax notoginseng formula (A&P) has been clinically shown to effectively slow down the progression of chronic kidney disease (CKD) and has demonstrated significant anti-fibrosis effects in experimental CKD model. However, the specific active ingredients and underlying mechanism are still unclear. The active ingredients of A&P were analyzed by Ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-HR-MS). A mouse model of CKD was constructed by 5/6 nephrectomy. Renal function was assessed by creatinine and urea nitrogen. Real-time PCR and Western Blot were performed to detect the mRNA and protein changes in kidney and cells. An in vitro fibrotic cell model was constructed by TGF-β induction in TCMK-1 cells. The results showed that thirteen active ingredients of A&P were identified by UPLC-HR-MS, nine of which were identified by analysis with standards, among which the relative percentage of NOB was high. We found that NOB treatment significantly improved renal function, pathological damage and reduced the expression level of fibrotic factors in CKD mice. The results also demonstrated that Lgals1 was overexpressed in the interstitial kidney of CKD mice, and NOB treatment significantly reduced its expression level, while inhibiting PI3K and AKT phosphorylation. Interestingly, overexpression of Lgals1 significantly increased fibrosis in TCMK1 cells and upregulated the activity of PI3K and AKT, which were strongly inhibited by NOB treatment. NOB is one of the main active components of A&P. The molecular mechanism by which NOB ameliorates renal fibrosis in CKD may be through the inhibition of Lgals1/PI3K/AKT signaling pathway.